Effects of individualized dietary counseling on nutritional status and quality of life in post-discharge patients after surgery for gastric cancer: A randomized clinical trial - Yan, Hongxia; He, Fang; Wei, Jianjian; Zhang, Qiuxiang; Guo, Chunguang; Ni, Jinnv; Yang, Fangyu; Chen, Yingtai (Frontiers in Oncology, 2023)
Background Currently, the supporting evidence for dietary counseling is insufficient. The aim of this study is to evaluate the impact of individualized dietary counseling on nutritional outcomes and quality of life (QOL) in patients undergoing surgery for gastric cancer. Methods This study was a prospective, single-center, randomized controlled trial. The patients after surgery for gastric cancer were randomly assigned (1:1) to the intervention group and the control group. In the intervention group, patients receive individualized dietary counseling based on individual calorie needs and symptom assessment at 24 h before discharge, 14, 21, 30, and 60 days postoperatively. Patients in the control group received routine dietary counseling. The primary endpoint was body mass index (BMI) loss at 30, 60, and 90 days after surgery; the secondary endpoints were calorie and protein intake at 30 and 60 days after surgery, blood parameters, the 90-day readmission rate, and QOL at 90 days after surgery. Results One hundred thirty patients were enrolled; 67 patients were assigned to the intervention group and 63 patients to the control group. Compared with the control group, patients in the intervention group were significantly less BMI loss at 30 days (−0.84 ± 0.65 vs. −1.29 ± 0.83), 60 days (−1.29 ± 0.92 vs. −1.77 ± 1.13), and 90 days (−1.37 ± 1.05 vs. −1.92 ± 1.66) after surgery (all P< 0.05). Subgroups analysis by surgery type showed that the intervention could significantly reduce BMI loss in patients undergoing total and proximal gastrectomy at 30 days (−0.75 ± 0.47 vs. −1.55 ± 1.10), 60 days (−1.59 ± 1.02 vs. −2.55 ± 1.16), and 90 days (−1.44 ± 1.19 vs. −3.26 ± 1.46) after surgery (all P< 0.05). At 60 days after surgery, calorie goals were reached in 35 patients (77.8%) in the intervention group and 14 patients (40.0%) in the control group (P = 0.001), and protein goals were reached in 40 patients (88.9%) in the intervention group and 17 patients (48.6%) in the control group (P< 0.001). Regarding the QOL at 90 days after surgery, the patients in the intervention group had a significantly lower level of fatigue, shortness of breath and stomach pain, better physical function, and cognitive function (P< 0.05). Conclusions Post-discharge individualized dietary counseling is an effective intervention to reduce post-gastrectomy patient weight loss and to elevate calorie intake, protein intake, and QOL.